General Solutions of Fully Fuzzy Linear Systems - T. Allahviranloo; S. Salahshour; M. Homayoun-nejad; D. Baleanu (Abstract and Applied Analysis)
We propose a method to approximate the solutions of fully fuzzy linear system (FFLS), the so-called general solutions. So, we firstly solve the 1-cut position of a system, then some unknown spreads are allocated to each row of an FFLS. Using this methodology, we obtain some general solutions which are placed in the well-known solution sets like Tolerable solution set (TSS) and Controllable solution set (CSS). Finally, we solved two examples in order to demonstrate the ability of the proposed method.